EVOLUTION OF MIGRATION PROCESSES: A HISTORICAL OVERVIEW AND CONTEMPORARY CHALLENGES - Садриддинов Шохрух Шукрулла угли (European Science Publishing, 2025)
This article provides a comprehensive analysis of the dynamics of migration processes, tracing the historical trajectory of human movements from the earliest dispersals out of Africa to the formation of modern transnational flows. The study examines key stages in the development of migration—from the initial migrations of Homo sapiens and the Neolithic transition to sedentary lifestyles, through migration waves in the ancient and medieval periods, to the eras of industrialization and globalization in the 20th–21st centuries. Particular attention is paid to the influence of economic, political, cultural, and ecological factors on migration processes, along with proposals for the effective management of contemporary migration challenges. By adopting an interdisciplinary approach, the article offers an integrated understanding of how migration has shaped societal development and transformed cultural-demographic structures.
Keywords: Migration, historical dynamics, transnational flows, globalization, demographic changes, economic migration, cultural interaction, interdisciplinary analysis.